Comparative evaluation of cytotoxic effects of milk from various species on leukemia cell lines - Rahmat, Asmah; Rosli, Rozita; Tan, Mui Hoon; Umar-Tsafe, Nasir; Ali, Abdul Manaf; Abu Bakar, Mohd Fadzelly (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
Objective: Previous studies have shown milk to contain cancer inhibitors. In this context, this study was conducted to screen the potential cytotoxic properties of four different types of milk, namely cow's milk, goat's milk, mare's milk and human milk. Methods: In evaluating the cytotoxic properties of milk, two different human leukemia cell lines namely, Raji and CEM-SS were used. The treated and untreated cells of milk were cultured at 37°C in 5% CO2 for 5 days according to standard guidelines. The CellTiter 96® Aqueous (MTS) assay was carried out on the first, third and fifth days to measure cell viability. The percentage of cell viability was determined by comparing the optical density of the treated cells against the untreated controls. One-way ANOYA at p<O.05 , Duncan's Multiple Range test and Independent T-test were carried out to determine the mean count differences of cell viability between and within cow's milk, goat's milk, mare's milk and human milk. Results: Interestingly, only mare's milk was found to cause statistically significant cytotoxicity on both the Raji (p<O.05) and CEM-SS (p<O.05) cells at 10% dilution. The cells treated with cow's milk, goat's milk and human milk showed no significant difference in cell viability when compared to the untreated controls where cell growth effects were observed instead. In addition, the cells treated with mare's milk underwent morphological changes that were indicative of apoptosis. Conclusion: The findings of this study show that among the four types of milk, mare's milk appears to possess cytotoxic properties against leukemia cell lines.